Estudo térmico da combustão de biomassa - Macedo, Lucas Carvalho Novaes de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The Brazilian energy matrix has been going through a change, where it occurs a decrease in energetic supply by the non-renewable fuels inducing an increase in renewable fuels supply. Therefore, the biomass is a clean and flexible source of energy. With the expansion of Brazilian agricultural production due to the amount of arable land, studies point out a perspective on agricultural production growth, consequently, an increase in biomass production in this country. For that reason, this work aimed to analyses the energy aspects of biomass, determining the superior and inferior calorific value, experimentally and through calculations. To the experimental determination of SCP, it was used the calorimeter C 5000 Control Package 1/12. The experimental results showed that the studied biomass, rice husk, sugarcane bagasse and corn straw, brought up an SCP of 14,16 MJ/kg, 16,71 MJ/kg and 16,92 MJ/kg, respectively

A matriz energética brasileira passa por uma mudança nos últimos anos onde ocorre o decréscimo da oferta energética a partir de combustíveis não renováveis e a ascensão da oferta por combustíveis renováveis. Sendo a biomassa uma fonte limpa e flexível de energia. O aumento da produção agrícola no Brasil e a quantidade de terra agriculturável apontam uma perspectiva de crescimento na produção agrícola, e, consequentemente, de biomassa no país. Este trabalho tem por objetivo analisar os aspectos energéticos de biomassa no tocante à determinação do poder calorífico superior, experimentalmente. Para a determinação experimental do PCS foi utilizado o calorímetro C 5000 Control Package 1/12. Os resultados experimentais mostraram que as biomassas estudadas, casca de arroz, bagaço de cana e palha de milho, apresentam o PCS de 14,16 MJ/kg, 16,71 MJ/kg e 16,92 MJ/kg, respectivamente
Keywords: Energia - Fontes alternativas; Biomassa; Resíduos agrícolas; Casca de arroz; Bagaço de cana; Palha de milho; Renewable energy sources